Metabolic Diversity and Therapeutic Potential of Holarrhena pubescens: An Important Ethnomedicinal Plant - Kulsoom Zahara; Sujogya Kumar Panda; Shasank Sekhar Swain; Walter Luyten (Biomolecules, 2020)
Holarrhena pubescens is an important medicinal plant of the Apocynaceae family that is widely distributed over the Indian subcontinent. The plant is extensively used in Ayurveda and other traditional medicinal systems without obvious adverse effects. Beside notable progress in the biological and phytochemical evaluation of this plant over the past few years, comprehensive reviews of H. pubescens are limited in scope. It has economic importance due to the extensive use of seeds as an antidiabetic. Furthermore, the plant is extensively reported in traditional uses among the natives of Asia and Africa, while scientifical validation for various ailments has not been studied either in vitro or in vivo. This review aims to summarize information on the pharmacology, traditional uses, active constituents, safety and toxicity of H. pubescens. Chemical analysis of H. pubescens extracts revealed the presence of several bioactive compounds, such as conessine, isoconnessine, conessimine, conimine, conessidine, conkurchicine, holarrhimine, conarrhimine, mokluangin A-D and antidysentericine. Overall, this review covers the ethnopharmacology, phytochemical composition, and pharmacological potential of H. pubescens, with a critical discussion of its toxicity, biological activities (in vitro and in vivo), the mechanism of action, as well as suggestions for further basic and clinical research.